The impact of endometriosis on depressive and anxiety symptoms and quality of life: a systematic review - Szypłowska, Małgorzata; Tarkowski, Rafał; Kułak, Krzysztof (Frontiers in Public Health, 2023)
Endometriosis is a common gynecological disorder affecting approximately 10–15% of women of reproductive age. The main complaints of patients with endometriosis are pain and fertility problems. Symptoms of endometriosis can impact the psychological functioning of the patients and significantly compromise their mental health. The aim of this review was to assess the prevalence of depressive and anxiety symptoms and quality of life in endometriosis patients. For this systematic review, we searched the PubMed, MEDLINE, ProQuest, EMBASE, Cochrane, CINAHL, Google Scholar, Scopus, and ScienceDirect electronic databases between up to March 2023 to identify potentially relevant studies. The systematic review in the present paper is reported in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidance. Of 4 records identified, 18 were eligible to be reviewed on the association between endometriosis and symptoms of depression and anxiety. Of 8901 records identified, 28 were reviewed on the association between endometriosis and quality of life. The reviewed articles showed a prevalence ranging from 9.8 to 98.5% for depressive symptoms and 11.5 to 87.5% for anxiety. The quality of life in patients with endometriosis was significantly impaired, regardless of the tool used for evaluation. This systematic review shows that endometriosis is associated with depressive and anxiety symptoms and impaired HRQoL. Broad correlating factors modulate mental health outcomes, indicating the complex relationship between the disease and the psychological health of the patients.